Leptospirosis Complicated by Secondary Hemophagocytic Lymphohistiocytosis in a Child: A Rare Association - Madhumita Nandi; Swarupananda Bera (Pediatric Infectious Disease)
Aims and background: Leptospirosis is caused by spirochetes of the genus Leptospira. In most patients, it is a very mild illness. However, some patients develop complications due to the involvement of multiple organ systems. Hemophagocytic lymphohistiocytosis (HLH) is characterized by prolonged fever, hepatosplenomegaly and cytopenias, hyperferritinemia and hypertriglyceridemia, hypofibrinogenemia, and hemophagocytosis in lymphoreticular system. It may occur primarily as a result of some genetic predisposition or secondarily associated with certain infections, autoimmune, and malignant conditions [secondary hemophagocytic lymphohistiocytosis (sHLH)]. Case description: We report a 9-year-old girl with secondary HLH associated with Leptospira infection treated successfully with appropriate antibiotics and intravenous immunoglobulin. Conclusion: Progressive cytopenia associated with deteriorating clinical condition with recurrence or nonabatement of fever should lead the clinician to suspect sHLH. Clinical significance: Leptospirosis precipitating HLH has rarely been reported.